KEWENANGAN PEMERINTAH PROVINSI BALI DALAM PEMUNGUTAN PAJAK PROGRESIF - Ida Bagus Prayoga (University of Udayana, 2016)
Motor vehicle tax is one source of revenue that give considerable contribution to the financing of government and regional development in bali Province. The imposition of a progressive tax rate on motor vehicles in Bali is the authorization from the Bali Provincial Regulation No. 1 of 2011. Own motor vehicle tax is one type of provincial tax provided for in Law No 28 of 2009. The purpose of this paper was to find out more about the Motor Vehicle Tax in Bali. The issue in this study is how the rates charged in the collection of Motor Vehicle Tax is charged at progressive field and how the reality of the new policy of the Government of Bali Province, whether the policy is the imposition of progressive tax rates are in accordance with the principles of taxation. Pajak kendaraan bermotor merupakan salah satu sumber pendapatan yang memberikan kontribusi yang cukup besar untuk pembiayaan pemerintah dan pembangunan daerah di Provinsi Bali. Pengenaan tarif pajak progresif kendaraan bermotor di Bali adalah wewenang yang diperoleh dari Peraturan Provinsi Bali No. 1 tahun 2011. Pajak kendaraan bermotor sendiri merupakan salah satu jenis Pajak Provinsi yang diatur dalam UU No 28 tahun 2009. Tujuan dari penulisan ini adalah untuk mengetahui lebih lanjut tentang Pajak Kendaraan Bermotor di Bali. Masalah dalam penelitian ini adalah bagaimana tarif yang dikenakan dalam pemungutan Pajak Kendaraan Bermotor yang dikenakan tarif progresif dan bagaimana realitas kebijakan baru dari Pemerintah Provinsi Bali, apakah kebijakan tersebut adalah pengenaan tarif pajak progresif yang sesuai dengan prinsip-prinsip perpajakan.